Synchronization of the Coupled Distributed Parameter System with Time Delay via Proportional-Spatial Derivative Control - Kun Yuan; Abdulaziz Alofi; Jinde Cao; Abdullah Al-Mazrooei; Ahmed Elaiw (Discrete Dynamics in Nature and Society)
By combining parabolic partial differential equation (PDE) theory with Lyapunov technique, the synchronization is studied for a class of coupled distributed parameter systems (DPS) described by PDEs. First, based on Kronecker product and Lyapunov functional, some easy-to-test sufficient condition is given to ensure the synchronization of coupled DPS with time delay. Secondly, in the case that the whole coupled system cannot synchronize by itself, the proportional-spatial derivative (P-sD) state feedback controller is designed and applied to force the network to synchronize. The sufficient condition on the existence of synchronization controller is given in terms of a set of linear matrix inequalities. Finally, the effectiveness of the proposed control design methodology is demonstrated in numerical simulations.